Review on programmed cell death and vertebrate embryonic development - LUAN Jingyun; XU Pengfei (浙江大学学报. 农业与生命科学版)
Vertebrate embryonic development is a complex process in which cells self-organize into a completely formed organism via cell behaviors such as division, proliferation, differentiation, migration, and programmed cell death (PCD). Among these cell behaviors, PCD exists in all stages of embryonic development, playing important roles in organogenesis, morphogenesis, and maintenance of tissue homeostasis. In this review, we summarized recent research progress on the regulation of vertebrate embryonic development by PCD, including the biological function and regulatory mechanism of PCD and clearance of dead cells during early embryonic development, focusing on the close link between PCD and embryonic developmental processes. We hope this review will help build a more comprehensive understanding of the roles of PCD in vertebrate embryonic development, and provide insights into how PCD is manipulated to improve the quality of embryonic development in the future.